2016
DOI: 10.1007/s11356-016-7131-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing persistent organic pollutants (POPs) in the Sicily Island atmosphere, Mediterranean, using PUF disk passive air samplers

Abstract: Diet plays a pivotal role in dictating behavioral patterns of herbivorous animals, particularly specialist species. The giant panda (Ailuropoda melanoleuca) is well-known as a bamboo specialist. In the present study, the response of giant pandas to spatiotemporal variation of bamboo shoots was explored using field surveys and GPS collar tracking. Results show the dynamics in panda-bamboo space-time relationships that have not been previously articulated. For instance, we found a higher bamboo stump height of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Many studies have demonstrated that for relatively short sampling durations (weeks or months) the variability between measured concentrations is rather high even in relatively small regions and between sites classified as background sites. Long-term monitoring makes it possible to reduce this variability because short-term fluctuations are averaged out.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that for relatively short sampling durations (weeks or months) the variability between measured concentrations is rather high even in relatively small regions and between sites classified as background sites. Long-term monitoring makes it possible to reduce this variability because short-term fluctuations are averaged out.…”
Section: Introductionmentioning
confidence: 99%
“…This semi-enclosed environment of high ecological and socio-economic relevance is largely impacted by POPs and related contaminants. 17,18,19 PCDD/Fs, PCBs and PBDEs are among the POPs found in the atmospheric compartment from various NW Mediterranean coastal environments (from rural to large cities), [20][21][22][23][24][25][26] and the central/Eastern basin [27][28][29][30][31][32][33] , but also farther from the coast in the entire Mediterranean Sea. [34][35][36] The European Mediterranean coast is by far the most studied and only few measurements (focussing in the SE Mediterranean) have been carried out in the African Mediterranean edge.…”
Section: Introductionmentioning
confidence: 99%
“…These substances are present in fabrics, electrical materials, dust; e.g., they induce pulmonary toxicity by promoting an inflammatory response in lung epithelial cells [43][44][45]. The same PBDE profile has been described in southern Europe by Besis et al [46], while Pozo et al identified, of 26 PBDEs routinely analyzed, the presence of three (PBDE-47, -99 and -100) in the coastal areas of Sicily [47]. These substances are highly carcinogenic, and they certainly interfere with the endocrine system (endocrine disruptors).…”
Section: Environmental Pollution and Health Of Respiratory Systemmentioning
confidence: 54%